Loxodontomys pikumche (Rodentia, Cricetidae): New specie for Argentina - Novillo, Agustina (2009)
We report the first record of occurrence of Loxodontomys pikumche Spotorno et al., 1998, in the Central Andes of Argentina. We briefly describe external characters, skull, karyotype, and habitat; also, we provide general comparisons with the other known species in the genus, L. micropus.